Identification of period and direction of monochromatic waves through the processing of optical images - Rapizo, Henrique; D'Ávila, Victor; Violante-Carvalho, Nelson; Pinho, Uggo; Parente, Carlos Eduardo (Anuário do Instituto de Geociências, 2014)
A new methodology to estimate the period and direction of monochromatic surface gravity waves is presented based on the processing of a sequence of images. The analysis focuses on the spatial-temporal variability of brightness on the image plane. One camera only is employed to record the water surface. The main motive is to come up with a simplified and practical configuration which allows its operational implementation either on the laboratory or on oil platforms or on top of buildings. The promising results correspond to experiments in a monochromatic wave tank. The image processing technique has proven to be a valuable tool for wave measurements.